2020
DOI: 10.1001/jama.2020.20122
|View full text |Cite
|
Sign up to set email alerts
|

Screening for High Blood Pressure in Children and Adolescents

Abstract: POPULATION This recommendation statement applies to children and adolescents aged 3 to 18 years not known to have hypertension or who are asymptomatic. EVIDENCE ASSESSMENTThe USPSTF concludes that the evidence to support screening for high blood pressure in children and adolescents is insufficient and that the balance of benefits and harms cannot be determined.RECOMMENDATION The USPSTF concludes that the current evidence is insufficient to assess the balance of benefits and harms of screening for high blood pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…Despite the latest guidelines of the American Pediatric Association to screen for hypertension among all adolescents, 23 a recent review by the US Preventive Task Force concluded that such a recommendation is not justified due to the lack of evidence regarding long-term clinical outcomes. 24 Our study suggests neurological sequela of established late-adolescent hypertension, in the form of stroke in young adulthood. This observation adds to the cumulative evidence of the potentially harmful effects of adolescent hypertension, 3,[6][7][8] even when controlling for such central risk factors as adolescent BMI and diabetes during adult life.…”
Section: Discussionmentioning
confidence: 59%
“…Despite the latest guidelines of the American Pediatric Association to screen for hypertension among all adolescents, 23 a recent review by the US Preventive Task Force concluded that such a recommendation is not justified due to the lack of evidence regarding long-term clinical outcomes. 24 Our study suggests neurological sequela of established late-adolescent hypertension, in the form of stroke in young adulthood. This observation adds to the cumulative evidence of the potentially harmful effects of adolescent hypertension, 3,[6][7][8] even when controlling for such central risk factors as adolescent BMI and diabetes during adult life.…”
Section: Discussionmentioning
confidence: 59%
“…Only a weak relation of diastolic blood pressure to RFMp (r = 0 .206, p < 0.001) appeared in the All group. Despite well-established policies for BP measurement in the clinical area of this Unit, results are not as consistent as other clinical parameters, and probably the doubts about BP screening (49,50) not only apply to these data but lead to reconsidering these policies.…”
Section: Discussionmentioning
confidence: 87%
“…Only a weak relationship of diastolic blood pressure with RFMp (r = 0 .206, p < 0.001) appeared in the total sample. Despite well-established policies for BP measurement in the clinical area of this unit with an elevated blood pressure section [56], the results are not as consistent as those of other clinical parameters, and doubts about BP screening [57,58] probably not only apply to these data but also lead to reconsidering these policies.…”
Section: Blood Pressurementioning
confidence: 82%